Kindergarten principal leadership and academic supervision of supervisors as contributing factors to kindergarten teacher performance - Hafnizar, Hafnizar; Daharnis, Daharnis; Putra, Febri Wandha (Jurnal Aplikasi IPTEK Indonesia, 2021)
Research based on phenomena that show a decline in teacher performance. The purpose of this study was to describe the contribution of kindergarten principal leadership and academic supervision to performing kindergarten teachers. This type of research is quantitative, with a descriptive correlational approach. The population in this study were kindergarten teachers, amounting to 43 people. Respondents in this study amounted to 43 people. The instrument used is a Likert model scale and a questionnaire about teacher performance, the leadership of the kindergarten principal, and the academic supervision of the education unit supervisor. Test the validity using the product moment correlation. For the reliability test using Cronbach’s alpha. The requirements analysis tests carried out are; normality test, linearity test and multicollinearity test. The data analysis technique used simple regression and multiple regression. The results showed that; 1) there is a contribution from the leadership of the kindergarten head to performing the kindergarten teacher, 2) there is the contribution of the academic supervision of the education unit supervisor to the kindergarten teacher’s performance, and 3) there is the contribution of the leadership of the kindergarten head and the academic supervision of the education unit supervisor to the kindergarten teacher performance.